Pengaruh Cost Recovery terhadap Pendapatan Perusahaan dan Goverment Take pada PT Chevron Pacific Indonesia - ZA, Kasman Arifin; Arifin, Iqbal Maulana (Jurnal Aplikasi Manajemen, 2014)
The aims of this study are: 1) analyzing empirically and examining the effect of cost recovery on APBN 2) analyzing empirically and examining the effect of cost recovery on sharing holder fund. Analysis unit of this research is upstream of oil and gas industry that is managed by Indonesian government with Production Sharing Contract for 44 companies or operator production sharing contract. The population of this research obtains from operator production sharing contract and BPMIGAS on manager level 62 persons, professional 51 persons and researcher from university 18 persons. The researcher was also secondary data during the year 1984 to 2009. The results show that six variables seemingly have directly significant relationship path and four variables show insignificant pattern of relationship. Variable which has effect is cost recovery to sharing holder fund, and the variable which do not have an effect is cost recovery to APBN.